PEMEROLEHAN BAHASA PERTAMA TERHADAP ANAK USIA 2 SAMPAI 4 TAHUN MENURUT TATARAN MORFOLOGI DAN SINTAKSIS - Endah, Nur; Rahmayanti, Dwi Apriliani; Supriatna, Enjang (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
The study aims to find out about the development of language in morphological and syntactic aspects. Research subjects were children aged 2 years 8 months who were in the research environment. The research method is descriptive because the study contains the description in the language pronunciation stages in children. The data collection techniques using recording and recording words spoken child. General conclusions on language acquired children aged 2 to 4 years can be developed with morphological and syntactic stages. Researchers found the process of obtaining the discussion among others is the first at the age of 2 to 4 years of morphology, the emergence of a more free form of free form. Both acquisition of syntax, the child is able to say a few words that can be a word. Third at the age of 2 to 4 years of morphological acquisition and the syntax of the child begins perfectly in the vowel sound and also accompanied by the sound of consonants.